The impact of wearing facemask on COPD patients: A protocol of a systematic review and meta-analysis - Chen, Xuwen; Sani, Ibrahim; Xia, Xiaoli; Li, Yi; Li, Caiyun; Yue, Feiyan; Wang, Xinhua; Bao, Shisan; Fan, Jingchun (PloS one, 2023)
Introduction Chronic obstructive pulmonary disease (COPD) is a common, irreversible but preventable disease characterized by persistent respiratory symptoms. The mortality rate of COPD is predicted to reach 5.4 million by the year 2060. Despite its heavy burden on healthcare expenditure worldwide, only 15% of cases are medically identified. The potential benefits of facemask-wearing for COPD patients remain a topic of debate. Methods We will conduct a systematic review of all randomized trials and non-randomized controlled trials to evaluate the impact of facemasks on COPD patients. Our review will be based on literature obtained through a comprehensive search strategy across multiple electronic databases, including the Cochrane Library, Embase, PubMed, Web of Science, the Chinese Biomedical Database (SinoMed), and China National Knowledge Infrastructure (CNKI), with no restrictions on language or date of publication. Two independent researchers will extract and assess all relevant data using pre-designed data extraction forms. The included studies will be assessed using the Cochrane RoB2 tool and the suggested risk of bias criteria proposed by the Effective Practice and Organization of Care reviews group of the Cochrane collaboration. The quality of evidence will be assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. We will use Review Manager 5.4 software for statistical analysis. Discussion In the context of COVID-19, it is important for COPD patients to wear facemasks. This study aims to conduct a comprehensive and systematic assessment of the impact of facemasks on the physiology and activity of COPD patients. Trial registration PROSPERO registration number CRD42022326265.